Anti-Inflammatory Activity of Thymol and Thymol-Rich Essential Oils: Mechanisms, Applications, and Recent Findings - Custódia Gago; Ana Serralheiro; Maria da Graça Miguel (Molecules)
Thymol, a monoterpenoid phenol present in the essential oils of several aromatic plants, has attracted considerable attention for its anti-inflammatory effects, often in combination with other bioactive compounds. This work explores the mechanisms behind the anti-inflammatory activity of thymol and thymol-rich essential oils, summarizing recent experimental findings. Inflammation, a key factor in numerous chronic diseases, can be modulated by targeting essential molecular pathways, such as MAPK, NF-κB, JAK/STAT, and arachidonic acid signaling. Thymol has been shown to influence these pathways, reducing the production of pro-inflammatory cytokines and mediators. Beyond its anti-inflammatory effects, thymol also exhibits a broad range of biological activities, including antimicrobial, antioxidant, and anticancer properties. The applications of thymol and thymol-containing essential oils in therapeutic formulations, food additives, and veterinary medicine are also reviewed. Despite promising preclinical results, challenges such as low bioavailability and toxicity at high doses limit their clinical use. Recent developments in drug delivery systems, such as encapsulation in micro- and nanoparticles, are suggested as strategies to enhance efficacy. Additionally, the synergistic effects of thymol with other natural products are examined, offering the potential for improved therapeutic outcomes.